ZALEŻNOŚĆ MIĘDZY POZIOMEM OPANOWANIA GRAMATYKI A WYBRANYMI CZYNNIKAMI KOGNITYWNYMI I AFEKTYWNYMI: ZARYS PROJEKTU BADAWCZEGO - Pawlak, Mirosław (Neofilolog, 2018)
Although there is a considerable body of research aiming to determine the effectiveness of different techniques and procedures in promoting the mastery of grammar structures in the target language, little is still known about how this effectiveness is mediated by individual difference (ID) variables, which, in turn, may determine learner engagement and translate into learning outcomes (Ellis, 2010; Pawlak, 2014, 2017b). For this reason, it is necessary to undertake research that would explore the link between grammar knowledge and ID factors. This is the rationale behind the research project funded by the Polish National Science Center outlined in the present paper. The project involves over 200 English philology and aims to establish the mediating effects of working memory, willingness to communicate, motivation, grammar learning strategies, and beliefs about grammar instruction with respect to the mastery of different types of English passive voice (i.e., different aspects and tenses), taking into account both explicit and implicit knowledge of this grammatical feature.